Offset timing of climate oscillations during the last two glacial‐interglacial transitions connected with large‐scale freshwater perturbation. (24th June 2015) - Jiménez‐Amat, Patricia; Zahn, Rainer
Abstract: Multidecadal to centennial planktic δ 18 O and Mg/Ca records were generated at Ocean Drilling Program Site 976 (ODP976) in the Alboran Sea. The site is in the flow path of Atlantic inflow waters entering the Mediterranean and captured North Atlantic signals through the surface inflow and the atmosphere. The records reveal similar climatic oscillations during the last two glacial‐to‐interglacial transitions, albeit with a different temporal pacing. Glacial termination 1 (T1) was marked by Heinrich event 1 (H1), post‐H1 Bølling/Allerød warming, and Younger Dryas (YD) cooling. During T2 the H11 δ 18 O anomaly was twice as high and lasted 30% longer than during H1. The post‐H11 warming marked the start of MIS5e while the subsequent YD‐style cooling occurred during early MIS5e. The post‐H11 temperature increase at ODP976 matched the sudden Asian Monsoon Termination II at 129 ka B.P. Extending the 230 Th‐dated speleothem timescale to ODP976 suggests glacial conditions in the Northeast Atlantic region were terminated abruptly and interglacial warmth was reached in less than a millennium. The early‐MIS5e cooling and freshening at ODP976 coincided with similar changes at North Atlantic sites suggesting this was a basin‐wide event. By analogy with T1, we argue that this was a YD‐type event that was shifted into the early stages of the last interglacial period. This scenario is consistent with evidence from northern North Atlantic and Nordic Sea sites that the continuing disintegration of the large Saalian Stage (MIS6) ice sheet in Eurasia delayed the advection of warm North Atlantic waters and full‐strength convective overturn until later stages of MIS5e. Key Points: Last Interglacial started within 1000 years or less Younger Dryas‐type rebound occurred during last interglacial Continuing ice melt delayed full interglacial conditions by several millennia